Spatial Mapping Of Coconut Plantation In Minahasa Regency, North Sulawesi Province Using Remote Sensing Data - Rotinsulu, Wiske Ch.; Runtunuwu, Semuel D.; Walangitan, Hengkie; Paat, Frangky J.; Zaini, Badrun (Jurnal Agroekoteknologi Terapan, 2022)
Kata kunci: Interpretasi visual, perkebunan, citra satelit